A Novel Method to Develop an Automobile Assembly Line System - Ali, A. J. Adham; Ahmad Nazif, Noor Kamar (Academic Journals, 2014)
The assembly line is an important component of the automobile production process. The function of the assembly line is to produce different models of vehicles with minimum work in the process. For better performance, activities on the assembly line should be performed to minimise the process steps and achieve other objectives. This study develops a new dynamic sequence-control system. Three methods, namely the Multi-Objectives Model, the Genetic Algorithm System and the Simulation Model, are integrated to enhance the efficiency of the assembly line by controlling the processing time within the workstations. The results show that the method was able to improve the working time performance and also increase throughputs.